Manifestasi Tan Malaka Bapak Republik Yang Terlupakan Pada Era Masa Kini (Ditinjau Dari Kontribusi Perjuangan) - Sopacua, Jems (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2022)
Tan Malaka was a militant, radical, and revolutionary fighter who contributed many original ideas towards achieving Indonesia's independence. Discussing Tan Malaka is highly contradictory because his name is often associated with Marxist communism, which is banned in Indonesia. However, he was not a fundamentalist Marxist; instead, he used Marxism as a tool in the struggle to achieve the goal of Indonesian independence. As a result, Tan Malaka's name has never been seriously introduced to the public, especially to the younger generation in the educational system. The purpose of this article is to analyze Tan Malaka's struggle in order to revive his legacy, which has been buried in oblivion, and to instil his fighting spirit and exemplary character in the process of shaping the current generation. The method used in writing this article is a literature study. The results of this article indicate that Tan Malaka's existence should be equated with the founders of Indonesia, with the hope that his ideas, as expressed in his works, can be used as a reference for building a better nation in the future. Though Tan Malaka is no longer with us, his fighting spirit can serve as an example for the present generation.